ANALISIS KEBIJAKAN DAN REGULASI PENDIDIKAN DAYAH BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2019: STUDI KASUS DI DAYAH ZURRIYATUL QUR’AN AL-MAARIF - Ulfanur Ulfanur; Agus Salim Salabi; Nurmayuli Nurmayuli (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyse the implementation of dayah education policies and regulations based on Law Number 18 of 2019 concerning Pesantren and Aceh Qanun Number 9 of 2018 concerning the Organisation of Dayah Education, with a case study at Dayah Zurriyatul Qur’an Al-Ma’arif. This research uses a descriptive qualitative approach with a case study type, through data collection techniques including in-depth interviews, participatory observation, and document study. The research subjects consist of 10 informants, including dayah leaders, institutional administrators, 2 teachers (teungku), 3 senior students, and 2 officials from the Aceh Dayah Agency (BDA) who are related to dayah policy and development. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. It concluded that the synchronization between national and regional policies has created an educational model of research results indicate that Dayah Zurriyatul Qur’an Al-Ma’arif has implemented most of the regulatory provisions in the Pesantren Law and Aceh Dayah Qanun, particularly in terms of institutional governance, curriculum, and institutional cooperation with the Aceh Dayah Agency (BDA). These regulations provide legal recognition and institutional strengthening for the dayah as an integral part of the Islamic education system in Aceh. However, there are still challenges such as limited human resources, funding, and curriculum adaptation that need attention. The study concludes that the synchronization between national and regional policies has created a model of Islamic education that harmonises traditional values with the modern education system.